Is banning Persistent Organic Pollutants efficient? A quantitative and qualitative systematic review in bats - Priscila Stéfani Monteiro-Alves; Elizabete Captivo Lourenço; Rodrigo Ornellas Meire; Helena Godoy Bergallo (Perspectives in Ecology and Conservation)
Among the several noxious characteristics of Persistent Organic Pollutants (POPs) is a low environmental degradation rate, as they remain in the environment for decades. One of the measures adopted to mitigate environmental contamination is the imposition of bans and restrictions to several chemical compounds. But are bans being efficient to reduce the amount of such chemicals in the environment? In this systematic review, we analyzed the efficacy of banning POPs using bats as biomonitors in terrestrial habitats. Although bats provide relevant ecosystem services, these animals are highly exposed to chemical organic pollutants such as POPs due to their feeding and behavioral habits. POP concentrations were observed in biological tissues of bats in the genus Myotis (United States), with levels decreasing over the years since the ban. We also noticed a shortage of studies in neotropical regions, where the information gap on several POPs in tropical systems is still a concern in terms of history and intensive use of these toxic chemicals. Few studies were found on emerging POPs or on POPs recently included in the Stockholm Convention. Besides, the specimens in the analyses in the studies reviewed were not separated by sex or age, which may conceal the potential risk of POPs to the conservation of bat populations. We recommend that future research extends beyond chronic POP contamination in bats to also include risk assessment trials, as wild populations may be affected in the long-term, as well as their role in the ecosystem and the economy, requiring long-term studies.